The impact of advanced patient age in liver transplantation: a European Liver Transplant Registry propensity-score matching study. Issue 6 (June 2022) - Gómez-Gavara, Concepción; Lim, Chetana; Adam, René; Zieniewicz, Krzysztof; Karam, Vincent; Mirza, Darius; Heneghan, Michael; Pirenne, Jacques; Cherqui, Daniel; Oniscu, Gabriel; Watson, Christopher; Schneeberger, Stefan; et al.
Abstract: Background: The futility of liver transplantation in elderly recipients remains under debate in the HCV eradication era. Methods: The aim was to assess the effect of older age on outcome after liver transplantation. We used the ELTR to study the relationship between recipient age and post-transplant outcome. Young and elderly recipients were compared using a PSM method. Results: A total of 10, 172 cases were analysed. Recipient age >65 years was identified as an independent risk factor associated with reduced patient survival (HR:1.42 95%CI:1.23–1.65, p < 0.001). After PSM, 2124 patients were matched, and the same association was found between elderly recipients and patient survival and graft survival (p < 0.001). As hepatocellular carcinoma and alcoholic cirrhosis were independent prognostic factors for patient and graft survival a propensity score-matching was performed for each. Patient and graft survival were significantly worse (p < 0.05) in the alcoholic cirrhosis elderly group. However, patient and graft survival in the hepatocellular carcinoma cohort were similar (p > 0.05) between groups. Conclusion: Liver transplantation is an acceptable and safe curative option for elderly transplant candidates, with worse long-term outcomes compare to young candidates. The underlying liver disease for liver transplantation has a significant impact on the selection of elderly patients.